External employment – a review of legal regulations in selected European countries - Strupp, Liliana (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The concept of external employment has no legal definition in the Polish legal system. Of the many forms of external employment that have been present on the Polish labor market for years, known as temporary work, employee outsourcing (employee leasing), contracting in the IT sector, or body leasing, only temporary work has been legally regulated. The purpose of this study is to present how such forms are regulated in several other European countries, and what labor market needs they address.